The Buddhist saints of the forest and the cult of amulets: a study in charisma, hagiography, sectarianism, and millennial Buddhism - Tambiah, Stanley Jeyaraja (Cambridge studies in social and cultural anthropology, 1984)
The central actors in this book are some reclusive forest-dwelling ascetic meditation masters who have been acclaimed as 'saints' in contemporary Thailand. These saints originally pursued their salvation quest among the isolated villages of the country's periphery, but once recognized as holy men endowed with charisma, they became the radiating centres of a country-wide cult of amulets. The amulets, blessed by the saints, are avidly sought by royalty, ruling generals, intelligentsia and common folk alike for their alleged powers to influence the success of worldly transactions, whether political, economic, martial or romantic.